Pengembangan Sistem Informasi Penjualan Menggunakan Model Rapid Application Development (RAD) di Toko Anto Kaibon - Susmiyanto, Susmiyanto; Muflih, Ghufron Zaida (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
The advancement of information technology has significantly transformed operational activities across various sectors, including small businesses such as convenience stores. This study aims to develop a desktop-based cashier information application for Toko Anto to improve transaction efficiency, accuracy, and speed. The research method used is Research and Development (R&D) with the Software Development Life Cycle (SDLC) approach using the Rapid Application Development (RAD) model. Data collection was conducted through observation, interviews, document studies, and literature reviews. The development stages include requirements planning, system design, construction, and implementation. The system is designed to digitally record sales transactions, manage product inventory data, and print purchase receipts. The implementation results show that the cashier application accelerates transaction processes, minimizes input errors, and facilitates the generation of daily sales reports. Unit testing using the black box method confirms that all features function according to the specified requirements. The application also significantly improves user satisfaction in daily operations. In conclusion, this RAD-based desktop cashier application effectively supports Toko Anto's business processes in a more modern and efficient way